2013
DOI: 10.1371/journal.pone.0079628
|View full text |Cite
|
Sign up to set email alerts
|

Productive Infection of Human Skeletal Muscle Cells by Pandemic and Seasonal Influenza A(H1N1) Viruses

Abstract: Besides the classical respiratory and systemic symptoms, unusual complications of influenza A infection in humans involve the skeletal muscles. Numerous cases of acute myopathy and/or rhabdomyolysis have been reported, particularly following the outbreak of pandemic influenza A(H1N1) in 2009. The pathogenesis of these influenza-associated myopathies (IAM) remains unkown, although the direct infection of muscle cells is suspected. Here, we studied the susceptibility of cultured human primary muscle cells to a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
(74 reference statements)
3
23
0
Order By: Relevance
“…While in vitro studies have demonstrated the ability of influenza to infect human skeletal muscle, this has not been reliably demonstrated in vivo as there have been only two cases in which influenza virus has been isolated from the muscle tissue of patients with rhabdomyolysis . Histopathologic evaluation of affected muscle argues against an inflammatory myopathy as biopsies reveal patchy necrosis with little inflammatory infiltration .…”
Section: Resultsmentioning
confidence: 99%
“…While in vitro studies have demonstrated the ability of influenza to infect human skeletal muscle, this has not been reliably demonstrated in vivo as there have been only two cases in which influenza virus has been isolated from the muscle tissue of patients with rhabdomyolysis . Histopathologic evaluation of affected muscle argues against an inflammatory myopathy as biopsies reveal patchy necrosis with little inflammatory infiltration .…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus is the most frequent cause of this disease, and it has been demonstrated that influenza virus can directly infect cultured human muscle cells 8. The particular involvement of distal lower limbs muscles and the marked calf oedema is well documented in the literature but is not clearly explained.…”
Section: Discussionmentioning
confidence: 99%
“…Using these receptors, influenza virus penetrates airway epithelial cells. The same authors also reported viral replication in rhabdomyocytes with resultant cell destruction [23]. …”
Section: Discussionmentioning
confidence: 99%